Anonymous
Anonymous asked in Science & MathematicsMathematics · 10 months ago

The equation is 13k = 6k/15t - 7t Make k the subject?

5 Answers

Relevance
  • 10 months ago

    13 k = 6 k/15 t - 7t

    13 k = (2 k t)/5 - 7 t

    65 k = t (2 k - 35)

    k(65 - 2 t) = -35 t

    k

    = -35 t / (65 - 2 t)

    = 35 t / (2 t - 65)

    • Log in to reply to the answers
  • ?
    Lv 7
    10 months ago

    13k = 6k/15t - 7t

    // Multiply through by 15t

    13k (15t) = 6k - 7t (15t)

    195 kt - 6k = - 105 t²

    // Factor out k

    k (195t - 6) = -105 t²

    // Divide through by (195t - 6)

    k = -105 t² / (195t - 6)....................ANS

    • Log in to reply to the answers
  • Como
    Lv 7
    10 months ago

    Presentation is open to doubt due to lack of brackets.

    • Random Stranger
      Lv 6
      10 months agoReport

      No it isn't! That's why we use the order of operations, to prevent ambiguity. Asker my have asked the wrong question but what was asked is NOT in doubt.

    • Log in to reply to the answers
  • 10 months ago

    I assume that the - 7t is a separate term

    in other words, your equation is NOT:

    13k = 6k / (15t - 7t)

    -----

    13k = (6k/15t) - 7t

    multiply both sides by (15t)

    (13k)(15t) = 6k - (15t)(7t)

    clean up

    195kt = 6k - 105t^2

    subtract 6k from both sides

    195kt - 6k = -105t^2

    factor out "k" on the left

    k(195t - 6) = -105t^2

    divide both sides by (195t - 6)

    k = (-105t^2) / (195t - 6)

    • Log in to reply to the answers
  • What do you think of the answers? You can sign in to give your opinion on the answer.
  • 10 months ago

    Presuming you mean:

    13k = 6k/(15t) - 7t

    Since "k" is in more than one term, we need to group them together. Start with multiplying both sides by the denominator (15t):

    195kt = 6k - 105t²

    Now move the terms with "k" to one side and all other terms to the other side:

    195kt - 6k = -105t²

    to simplify a little, multiply both sides by -1. I'll flip the two terms around the subtraction on the left side:

    6k - 195kt = 105t²

    And now I can divide both sides by 3 to simplify further before we move on:

    2k - 65kt = 35t²

    Now we can factor out the k:

    k(2 - 65t) = 35t²

    and divide:

    k = 35t² / (2 - 65t)

    • Log in to reply to the answers
Still have questions? Get answers by asking now.